Community-funded integrated care outreach clinics as a capacity building strategy to expand access to health care in remote areas of Uganda - Rebecca G. Kinney (Taylor & Francis Group, 2021)
Most Ugandans live in rural, medically underserved communities where geography and poverty lead to reduced access to healthcare. We present a novel low-cost approach for supplemental primary care financing through 1) pooling community wealth to cover overhead costs for outreach clinic activities and 2) issuing microfinance loans to motorcycle taxi entrepreneurs to overcome gaps in access to transportation. The intervention described here, which leverages community participation as a means to extend the reach of government health service delivery, was developed and implemented by Health Access Connect (HAC), a non-governmental organization based in Uganda. HAC began its work in August 2015 in the Lake Victoria region and now serves over 40 sites in Uganda across 5 districts, helping government health-care workers to provide over 1,300 patient services per month (and over 35,000 since the program’s inception) with an average administrative cost of $6.24 per patient service in 2020. In this article, we demonstrate how integrated and appropriately resourced monthly outreach clinics, based on a microfinance-linked model of wealth pooling and government cooperation, can expand the capacity of government-provided healthcare to reach more patients living in remote communities. This scalable, sustainable, and flexible model is responsive to shifting needs of patients and health systems and presents an alternative approach to healthcare financing in low-resource settings. More rigorous evaluation of health outcomes stemming from such community-based models of service delivery is warranted.